Engaging the Narrative on Children Literature through the Teaching Extensive Reading - harits, Imron wakhid (Advances in Social Sciences Research Journal, 2017)
Teaching children literature engages with some of interconnected aspects such as psychology and the literature a well. Such connection represents the emotional and intellectual interaction during the process of teaching and learning children literature. The method for example the approach tries intertwining and supporting during the process of teaching and learning. The life experiences of the reader and the prior knowledge are essential in the teaching of children literature because an intellectual and emotional connection need reconstruct their prior knowledge and experiences to get the new preposition in understanding the children literature texts. This paper examines the teaching children literature in the extensive reading class and its interaction with historical and educational values as well as its literary devices. It also figures aout the process of the readers using their cultural and tradition experiences to engage with the children literature. The terms of engagement is derived from Nikolajeva cognitive criticism, it is the ways of readers how to understand the children literature from inside and outside communication.